(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The influence of COVID-19 on in hospital mortality and short-term outcome of acute ischemic stroke is not well known. Objective: The purpose of the present study was to analyze the overall impact of COVID-19 patients and 30-day outcomes of acute ischemic stroke patients. Methodology: This was a hospital-based case-control study from February to May 2021 conducted in stroke unit of National Institute of Neurosciences and Hospital. Consecutive ischemic stroke patients contracting COVID-19 infection was considered as case group and similar patients, negative for SARS CoV-2 on RT-PCR from nasal swab were considered for control group following the inclusion and exclusion criteria. Results: A total number of 50 cases and 99 similar control were taken. Although a significant proportion of control group were male (76.8% vs 50%), there was similar age distribution in both groups. Diabetes and Multiple comorbid conditions and lymphopenia were significantly (p value of <0.001) more common among the case (1% versus 22%, 28.3% versus 56% and 5.1% versus 54%) in contrast to hypertension and lymphocytosis which was more frequent in control group (42.4% versus 10% and 94.9% versus 46%). Though the cases had a significantly (p value <0.001) higher NIHSS score at admission (median IQR 7 versus 13) and longer hospital stay (median IQR 6 days versus 14 days). Male stroke patients were 4.7 times more likely to die in-hospital compared to female patients. The risk of mortality were 5 times higher among cases. Conclusion: COVID positive stroke cases have more severe disease at admission and longer hospital stays and the risk of mortality is 5 times higher in COVID positive stroke cases with a significant male dominance. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):11-15